2013
DOI: 10.1172/jci66301
|View full text |Cite
|
Sign up to set email alerts
|

Adoptively transferred TRAIL+ T cells suppress GVHD and augment antitumor activity

Abstract: Current strategies to suppress graft-versus-host disease (GVHD) also compromise graft-versus-tumor (GVT)responses. Furthermore, most experimental strategies to separate GVHD and GVT responses merely spare GVT function without actually enhancing it. We have previously shown that endogenously expressed TNF-related apoptosis-inducing ligand (TRAIL) is required for optimal GVT activity against certain malignancies in recipients of allogeneic hematopoietic stem cell transplantation (allo-HSCT). In order to model a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 33 publications
0
27
0
Order By: Relevance
“…This manuscript advances the field of cellular therapy by documenting the potential of separating GVHD from GVL: the prevention of GVHD not only without loss of GVL, but actual enhancement of GVL. used these cells in adoptive transfer experiments (6). As expected, they observed that TRAIL + T cells were highly active in vitro and in vivo in a murine model.…”
Section: Conflict Of Interestmentioning
confidence: 54%
See 3 more Smart Citations
“…This manuscript advances the field of cellular therapy by documenting the potential of separating GVHD from GVL: the prevention of GVHD not only without loss of GVL, but actual enhancement of GVL. used these cells in adoptive transfer experiments (6). As expected, they observed that TRAIL + T cells were highly active in vitro and in vivo in a murine model.…”
Section: Conflict Of Interestmentioning
confidence: 54%
“…As mentioned above, cells overexpressing TRAIL could also be quite useful as an "off-the-shelf" third-party infusion following lymphodepletion in a patient, resulting in GVL activity during the lymphopenic period, followed by rejection of the allogeneic TRAIL + cells after recovery of host immunity. Indeed, the work by Ghosh et al (6) suggests that TRAIL + T cells could exert their antitumor effects during this period of lymphodepletion, ridding the patient of the malignancy without altering their ability to fight viral infections. This manuscript advances the field of cellular therapy by documenting the potential of separating GVHD from GVL: the prevention of GVHD not only without loss of GVL, but actual enhancement of GVL.…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 2 more Smart Citations
“…Over the years, the concept of allo-HSCT has shifted toward a strategy of graft-versus-tumor (GVT) activity (Jenq & van den Brink 2010;Ghosh et al 2013Ghosh et al , 2014. Since GVH outcomes are often a complication of allo-HSCT, resulting in significant morbidity and mortality, and strategies to suppress GVH often result in broad immunosuppression (leading to immune deficiency/compromised anti-tumor surveillance), it has been important to explore targeting of molecular pathways that could accomplish separation of GVHD from GVT activity.…”
Section: Introductionmentioning
confidence: 99%